Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1111/j.1365-2133.1985.tb02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of polyneuropathy during thalidomide therapy

Abstract: Seven patients with prurigo nodularis and one with aphthous stomatitis were given 40-115 g of thalidomide for 1 to 6 years. They all developed a predominantly sensory peripheral neuropathy mainly involving the lower limbs. Five patients had an unpleasant tight feeling around the feet. Nerve conduction studies showed small sensory action potentials from the lower limbs with normal or only mild slowing of sensory conduction velocity indicating an axonal neuropathy. The dermatological disorder improved dramatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
3
4

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 18 publications
1
51
3
4
Order By: Relevance
“…9 It has been suggested that neuropathy might possibly be related to cumulative dose or duration of treatment. 22 However, one of our two cases developed neuropathy after 9 months of thalidomide, which is a shorter treatment period than many of those reported by others.…”
Section: Discussioncontrasting
confidence: 39%
“…9 It has been suggested that neuropathy might possibly be related to cumulative dose or duration of treatment. 22 However, one of our two cases developed neuropathy after 9 months of thalidomide, which is a shorter treatment period than many of those reported by others.…”
Section: Discussioncontrasting
confidence: 39%
“…Sensory symptoms may persist, and sometimes get worsen, after withdrawal of the drug and the pathologic findings suggest axonal neuropathy 34 . Although the frequency and the severity of neuropathy are not always found to be related to total dosage 34 , Wulff et al, confirmed that the neuropathy began after a total of 40-50g of thalidomide in most patients 35 . Despite the increased use of thalidomide around the world, we worry about the possible side effects, mainly teratogenicity and neuropathy of this drug 36 , but we believe that more than prohibit their production, the governments need to do more restrict laws to permit their use.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…This is believed to be related to the total dose administered [19,20]. A previous study showed that of seven patients with prurigo nodularis, given 40-115 g of thalidomide for 1-6 years, all developed peripheral neuropathy [21]. The reason for this was not clear until now: the higher dose of thalidomide (200 mg/kg/ day) that we used in rats, in comparison with doses used in humans (6-15 mg/kg/day) [22], may be responsible for induction of neuropathy or neurotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%